(untitled) (Theatrum historiae, 2020)
Although midwives were incorporated into the administrative system governing the conditions of birth delivery, female midwifery became the target of verbal attacks from the leading authorities of scientific medicine. Physicians addressed midwives often with superior hostility. In professional medical journals, the opinion was repeatedly represented by articles accentuating the archaic element of midwives’ obstetric practice and, in particular, the lack of education and subsequent ability to absorb modern knowledge to improve obstetric practice. Professional discourse was constantly questioning the female midwives’ capabilities, which, together with constantly increasing number of female midwives, resulted in the lack of guaranteed financial support for female midwives’ professional practice. Thus, as a profession, midwifery mostly could not provide an opportunity in terms of economic and social independence.